Paper and Salt: Biodegradable NaCl-Based Humidity Sensors for Sustainable Electronics - Falco, Aniello; Marín-Sánchez, Antonio; Loghin, Florin C.; Castillo, Encarnación; Salinas-Castillo, Alfonso; Salmerón, José F.; Rivadeneyra, Almudena (Frontiers in Electronics, 2022)
Flexible and thin-film humidity sensors are currently attracting the attention of the scientific community due to their portability and reduced size, really useful for several application in Internet o Things (IoT) industry. Furthermore, in order to perform an efficient and profitable mass production, it is necessary to develop cost-effective and reproducible fabrication process and materials. Green fabrication methods and biodegradable materials would also allow to minimize the environmental impact and to create a sustainable IoT development. In this paper, a humidity flexible sensors based on a common salt (NaCl) sensing layer are reported. Our sensors and the fabrication techniques employed such as dip and spray coating provide a biodegradable, low cost and highly reproducible device. One of the sensors reported presents a typical resistive behaviour from 40% RH up to 85% RH with a sensitivity of -0.21 (Z/%RH). The performance of the sensors obtained with several fabrication techniques is studied and reported at multiple frequencies from 100 Hz to 10 MHz, showcasing its versatility and robustness.